Nuclear Receptors in the Pathogenesis and Management of Inflammatory Bowel Disease - Longgui Ning; Xinhe Lou; Fenming Zhang; Guoqiang Xu (Mediators of Inflammation)
Nuclear receptors (NRs) are ligand-dependent transcription factors that regulate the transcription of target genes. Previous epidemiological and genetic studies have documented the association of NRs with the risk of inflammatory bowel disease (IBD). Although the mechanisms of action of NRs in IBD have not been fully established, accumulating evidence has demonstrated that NRs play complicated roles in regulating intestinal immunity, mucosal barriers, and intestinal flora. As one of the first-line medications for the treatment of IBD, 5-aminosalicylic acid (5-ASA) activates peroxisome proliferator-activated receptor gamma (PPARγ) to attenuate colitis. The protective roles of rifaximin and rifampicin partly depend on promoting pregnane X receptor (PXR) expression. The aims of this review are to discuss the roles of several important NRs, such as PPARγ, PXR, vitamin D receptor (VDR), farnesoid X receptor (FXR), and RAR-related orphan receptor gammat (RORγt), in the pathogenesis of IBD and management strategies based on targeting these receptors.